The presence and architecture of Islamic health providers in Egypt - Abdulhady, Sarah (Department of Public Health and Family Medicine, 2020)
Weakening health systems in the Middle East and North Africa (MENA) region has led to a shift towards a greater acknowledgement of the involvement of non-state providers in health care services and delivery. A wide range of non-state health providers exist in the region, one type being Islamic health providers (IHPs) which fall under the category of non-state, not-for profit health providers. There is very little information available about the non-state sector in the MENA region, and almost nothing about IHPs, although anecdotally they are described as providers of choice, said to provide high quality services at low cost. This research aims to explore the public/private mix in the MENA region, delving into the types of collaborations that occur between the public and non-state sector. It will then narrow down in a single case study focusing on looking at IHPs in on MENA country (Egypt), and consider how IHPs 'fit’ within their national health system. Egypt was chosen for this study as IHPs have a long presence there, as Egypt is the birthplace of many Islamic groups such as the Muslim Brotherhood, which then migrated to neighboring countries. Common themes found in the case study was the lack of regulations for both the non-state sector and IHPs, competition in service provision with the public sector, and inequality in provision of health services (the latter issue observed in the broader non-state sector in the MENA region, but not specifically in IHPs). With regards to IHPs in Egypt, they were found to serve nearly 20% of the population. Exact numbers of the presence of IHPs in the country is difficult to obtain, as they are largely invisible in literature and are often categorized as non-governmental organizations (NGOs). Estimates show that there are around 5000 NGOs providing primary health care (PHC) and other health services. Most of these facilities are concentrated in urban areas. It was found that the 'Islamic’ label of IHPs is utilised either to gain donations, to denote the fact that this is a charitable institution, or because the facility is attached to a mosque. Most of the IHPs in the country practice a form of social rather than political Islam, making them not that different from other non-state secular facilities.